Studi Perbandingan Pola Asosiasi Penjualan Sparepart Menggunakan Algoritma Apriori Di PT Astra International BMW Semarang - Raka Lintang Aditya; Sulastri Sulastri (STEKOM PRESS, 2024)
All PT Astra International BMW Semarang transactions are recorded in the database but the problem is that the stock management is efficientless so the part stock that buyers are interested is not available. This research aims to conduct a comparative mining results using the association rule with apriori algorithm for year 2021, 2022 and 2023 sales transaction dataset with total of 43.694 records using the Rstudio. Data mining process in each year uses the same parameters for each itemset combination. The best association pattern occurs in 2023 with support value 0.05913841 and confidence value 100%. This can be concluded that the rules formed from each year could be different eventhough using same parameters. The item that always appears in the association rule from 2021 – 2023is Z99000000333 (BMW Engine OIL) which is often purchased with items named “Set fil-oil” so it can be a recommendation for item stocking in the warehouse.